PENGGUNAAN MODEL PEMBELAJARAN PROJECT BASED LERNING DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL DI KELAS IV SDN LUBUK HARJO - Hendri Priyatno; Nazurty; Sukendro (Postgraduate, University of Mataram, 2025)
This research is motivated by the lack of enjoyable learning models that enhance students' critical thinking and problem-solving skills as an effort to improve learning outcomes in IPAS for fourth-grade students. The solution to this issue is the implementation of the Problem-Based Learning model. This study aims to determine the effect of using the Problem-Based Learning model on the learning outcomes of fourth-grade students at SD Negeri Lubuk Harjo. This research is a Classroom Action Research (CAR) study. Based on the analysis of evaluation test scores, there was an improvement in students' cognitive learning outcomes. The collected data were analyzed using descriptive statistical analysis, and the results showed that in the first cycle, the percentage of students who achieved mastery learning was 79.47%, which increased to 91.58% in the second cycle. Thus, it can be concluded that the use of the Problem-Based Learning model in Natural and Social Sciences learning can improve students' learning outcomes.